WU-LING-SAN FORMULA PROPHYLAXIS AGAINST RECURRENT CALCIUM OXALATE NEPHROLITHIASIS - A PROSPECTIVE RANDOMIZED CONTROLLED TRIAL - Lin, Eugene; Ho, Lin; Lin, Mao-Sheng; Huang, Min-Ho; Chen, Wen-Chi (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Wu-Ling-San (WLS) formula has been proved to prevent calcium oxalate nephrolithiasis both in vitro and in vivo. This is the first prospective, randomized and placebo-controlled clinical trial of WLS in calcium oxalate nephrolithiasis prevention. All patients who enrolled were asked to drink enough fluid to urinate at least 2 L daily during the study period. A 24-hour urine collection was performed to establish the baseline levels of multiple urinary parameters before taking the medicine. The patients were randomized and divided into two groups. The medication group took 2 gm WLS formula three times daily for 1 month. The control group took 2 gm placebo three times daily for 1 month. A 24-hour urine collection was performed to evaluate multiple urinary and serum parameters from all patients during the study period. A total of 39 patients were enrolled and 28 patients completed the study. Fourteen patients were allocated to WLS group and 14 patients to placebo group. After treatment, the mean urine output level increased to 2796.4  525.7 ml/day (percentage of change, 13.9 %) in the WLS formula group. With placebo therapy, the mean decreased slightly to 2521.4  762.7ml/day (percentage of change, -5.7 %). The percentage of change was significantly different between the two groups (independent t-test, P=0.02). No patient complained of side effects, such as fatigue, dizziness, musculoskeletal symptoms, or gastrointestinal disturbance. WLS formula is a promising adjunct to surgical and medical management of kidney stones. Active therapy with WLS formula has a positive effect on diuresis without leading to electrolyte imbalance.